2016
DOI: 10.1177/1043659616680268
|View full text |Cite
|
Sign up to set email alerts
|

Sharing for Health: A Study of Chinese Adolescents’ Experiences and Perspectives on Using Social Network Sites to Share Health Information

Abstract: Future interventions should provide adolescents with interesting and culturally sensitive health information and educate them to critically evaluate health information on social network sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Other researchers have found that Facebook users critically appraise the value of the health content they access (Zhang et al . ) and carefully consider the kind of information about their health and illness experiences to share with other users (Armstrong et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that Facebook users critically appraise the value of the health content they access (Zhang et al . ) and carefully consider the kind of information about their health and illness experiences to share with other users (Armstrong et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of emotional support provided by peers in Facebook for people living with diabetes and mental health conditions has also been demonstrated (Fergie et al 2016, Kingod 2018. Other researchers have found that Facebook users critically appraise the value of the health content they access (Zhang et al 2016) and carefully consider the kind of information about their health and illness experiences to share with other users (Armstrong et al 2012). The affordances of Facebook may invite different engagements compared with other online platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The methodological approaches identified in the international publications selected for this literature review follow three dominant techniques, with a more or less narrative objective, and that can be associated with each other: interviews, the "draw and write" method, and focus groups. Using drawings and carrying out focus groups sessions are the most represented methods: five made use of drawings (19,(22)(23)(24) and five had focus groups (15)(16)(17)(18)(19)(20)(21). Four studies carried out interviews (14,22,26) and one involved photoelicitation (17).…”
Section: Principal Methodologies Usedmentioning
confidence: 99%
“…The result of this form of research reflects the reality of the interaction between the attitudes of children and adolescents, and the social processes within the group. This, for example, promoted the emergence of health information sharing habits of Chinese adolescents on social network websites (18). This technique also allows the evaluation of needs, expectations, satisfaction, or a better understanding of opinions, motivations, or behaviors.…”
Section: Principal Methodologies Usedmentioning
confidence: 99%
See 1 more Smart Citation